Nanosciences outreach activities in the indiginous comunities of méxico (2013)
We always say that science and technology are the tools that are needed to make progress in countries in development. We can say the same in the case of the peoples and communities: knowledge about science and technology indicate their state of development. Many of the indigenous communities are living in poverty and do not have the best conditions for a dignified human development. The fight against social marginalization of people in the indigenous communities should be one of the policy areas most relevant to the development of Mexico. That is why we believe that policies targeting the development of indigenous groups should also include as a fundamental pillar education on science and technology. Together, conservation and recovery programs of indigenous languages must be accompanied by a process of incorporation scientific terms that allow the assimilation of science in the language of the communities.